Liquid chromatography-tandem mass spectrometry for the determination of methylprednisolone in rat plasma and liver after intravenous administration of its liver-targeted dextran prodrug - Zhang, Shuang-Qing (2009)
A specific and sensitive liquid chromatography (LC)-tandem mass spectrometric method for quantitative determination of methylprednisolone (MP) in rat plasma and liver was developed and validated using triamcinolone acetonide as an internal standard. Liquid-liquid extraction using tert-butyl methyl ether was used to extract the drug and the internal standard from plasma and liver. The separation of MP was performed on a C(18) column with a mobile phase of acetonitrile:0.5% formic acid aqueous solution (85:15, v/v) over 4 min. The assay was based on the selected reaction monitoring transitions at m/z 375→161 for MP in plasma, 375→357 for MP in liver, and 435→415 for internal standard in both plasma and liver. The lower limit of quantification was 20 ng/mL based on 100 μL of plasma or liver homogenate. Intra- and inter-day assay variations were ≤15%, and the accuracy values were between 85.8 and 118%. The extraction recoveries ranged from 76.8 to 79.2% for plasma and 76.8 to 80.8% for liver across the calibration curve range. The method was successfully applied to measurement of low concentrations of regenerated MP in plasma and liver after intravenous administration of a single dose (5 mg/kg) of a liver-targeted dextran prodrug of MP to rats.